How to have difficult conversations about race : practical tools for necessary change in the workplace and beyond - Christian, Kwame (BenBella Books, Inc., 2022)
"How to Have Difficult Conversations About Race equips you with the skills you need to make crucial conversations about race easier and more productive"--